Exploration of the Use of Quizizz Gamification Application: Teacher Perspective - Kristiani, Theresia; Sudiyanto; Usodo, Budi (Universitas Pendidikan Ganesha, 2022)
The development of ICT technology has an impact on the development of the game industry, which makes teachers more creative in designing their learning processes. However, teachers have not fully implemented the learning process using gamification-based media. This study aims to explore the teacher's perspective on the use of the Quizizz gamification application. This type of research is qualitative. The research subjects used consisted of 16 classroom teachers from 5 elementary schools. The data collection tool only uses structured interviews with classroom teachers. The data analysis technique uses a descriptive qualitative analysis using Miles and Huberman. The results show that using gamification, especially Quizizz, is beneficial and supports educators in learning. However, many educators admit that they have obstacles: they are unfamiliar with the gamification system, have difficulty in making gamification, have no training and socialization, and educators do not yet know the function of the advantages and disadvantages of gamification itself. These challenges and obstacles certainly require the support of the relevant stakeholders. The implication of this research is to improve the potential weaknesses of educators in order to become exemplary educators in the 21st century.